PRIORITY DIRECTIONS OF USING PUBLIC-PRIVATE PARTNERSHIP IN THE COUNTRIES OF CENTRAL EUROPE (Innovative professional education, 2023)
Public-private partnerships in Central European countries, despite the European Commission's active position in promoting this issue, are quite heterogeneously developed. Germany takes the lead in the implementation of public-private partnership projects, while other countries are characterized by a neutral attitude to this mechanism. The largest number of projects implemented under public-private partnerships are in the energy, transport, water and sanitation, telecommunications, education, and healthcare sectors.
Keywords: PPPs in Central Europe, public-private partnerships (PPPs), infrastructure PPP projects, educational PPP projects, healthcare PPP projects